2020
DOI: 10.1002/glia.23826
|View full text |Cite
|
Sign up to set email alerts
|

Nurr1Cd11bcreconditional knockout mice display inflammatory injury to nigrostriatal dopaminergic neurons

Abstract: Nuclear receptor related 1 protein (NURR1) is essential for the development and maintenance of midbrain dopaminergic (DAergic) neurons. NURR1 also protects DAergic neurons against neuroinflammation. However, it remains to be determined to what extent does NURR1 exerts its protective function through acting autonomously in the microglia. Using Cre/lox gene targeting system, we deleted Nurr1 in the microglia of Nurr1 Cd11bcre conditional knockout (cKO) mice. The Nurr1 Cd11bcre cKO mice displayed age-dependent mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Subsequently, we investigated the apoptosis and necrosis of HT22 cells at 24 h. Similar to CCK-8, AQ reduced the percentage of apoptosis and necrosis while increased the percentage of survival cells (Figure3(d)).3.4. Stimulation of Nurr1 with AQ Inhibited the Proinflammatory Microglia/Macrophage and Alleviated the Neuroinflammation.Numerous researches had been demonstrated the key role of Nurr1 in anti-inflammation in multibrain diseases[10,13,33,34]. We thus investigated the amount of proinflammatory phe-notype of microglia/macrophage and the inflammation response.…”
mentioning
confidence: 99%
“…Subsequently, we investigated the apoptosis and necrosis of HT22 cells at 24 h. Similar to CCK-8, AQ reduced the percentage of apoptosis and necrosis while increased the percentage of survival cells (Figure3(d)).3.4. Stimulation of Nurr1 with AQ Inhibited the Proinflammatory Microglia/Macrophage and Alleviated the Neuroinflammation.Numerous researches had been demonstrated the key role of Nurr1 in anti-inflammation in multibrain diseases[10,13,33,34]. We thus investigated the amount of proinflammatory phe-notype of microglia/macrophage and the inflammation response.…”
mentioning
confidence: 99%
“…Nurr1, also known as NR4A2/NOT/TINUR, is a member of the orphan nuclear receptor family 4 (NR4A), necessary for the mdDA neurons’ development, maturation, and functional maintenance [ 46 , 69 , 70 ]. It is also involved in neuroprotection and neuroinflammation regulation by inhibiting pro-inflammatory factors in microglial and astrocytes cells [ 71 , 72 , 73 ]. Notably, in mdDA neurons, the decreased levels of Nurr1 were characterized during aging, which may be related to the increased morbidity of PD [ 74 , 75 ].…”
Section: Tfs In Dopamine Cell Therapymentioning
confidence: 99%
“…Previous studies have found that most transplanted NSCs fail to differentiate into neurons but glial cells and survive after transplantation [ 66 ], which might significantly contribute to a poor host cellular environment. In light of the role of Nurr1 in glial cells [ 40 , 72 ], co-culture of embryonic mesenchymal NSCs and primary microglial cells overexpressing Nurr1 prolonged the survival of transplanted NSCs, decreased the number of microglial cells and showed long-term survival [ 86 , 87 ]. Recent innovative research has found that co-grafting NNSC and NMG (NSCs and microglia both with Nurr1 overexpression) improved the behavior of PD rats.…”
Section: Tfs In Dopamine Cell Therapymentioning
confidence: 99%
“…Microglia appear to be heterogeneous with diverse functional phenotypes that range from pro-inflammatory M1 phenotypes to immunosuppressive M2 phenotypes ( Tang and Le, 2016 ; Zhang et al, 2017 ; Wolters et al, 2021 ). Once sensing damage signals or toxic aggregated proteins inside or outside the cell, microglia will switch from resting to active ( Zhong et al, 2018 ; Dong et al, 2020 ). The continuous crosstalk between microglia and neurons is dependent on microglia housekeeping functions and contributes to the homeostasis of CNS ( Marinelli et al, 2019 ).…”
Section: Extracellular Vesicles In Glia-neuron Communicationmentioning
confidence: 99%